Genomic analyses show extremely perilous conservation status of African and Asiatic cheetahs (Acinonyx jubatus). Issue 16 (17th July 2022) - Prost, Stefan; Machado, Ana Paula; Zumbroich, Julia; Preier, Lisa; Mahtani‐Williams, Sarita; Meissner, Rene; Guschanski, Katerina; Brealey, Jaelle C.; Fernandes, Carlos Rodríguez; Vercammen, Paul; Hunter, Luke T. B.; Abramov, Alexei V.; et al.
Abstract: We live in a world characterized by biodiversity loss and global environmental change. The extinction of large carnivores can have ramifying effects on ecosystems like an uncontrolled increase in wild herbivores, which in turn can have knock‐on impacts on vegetation regeneration and communities. Cheetahs ( Acinonyx jubatus ) serve important ecosystem functions as apex predators; yet, they are quickly heading towards an uncertain future. Threatened by habitat loss, human‐wildlife conflict and illegal trafficking, there are only approximately 7100 individuals remaining in nature. We present the most comprehensive genome‐wide analysis of cheetah phylogeography and conservation genomics to date, assembling samples from nearly the entire current and past species' range. We show that their phylogeography is more complex than previously thought, and that East African cheetahs ( A. j. raineyi ) are genetically distinct from Southern African individuals ( A. j. jubatus ), warranting their recognition as a distinct subspecies. We found strong genetic differentiation between all classically recognized subspecies, thus refuting earlier findings that cheetahs show only little differentiation. The strongest differentiation was observed between the Asiatic and all the African subspecies. We detected high inbreeding in the Critically Endangered Iranian ( A. j. venaticus ) and North‐western ( A. j. hecki ) subspecies, and show that overall cheetahs, along with snow leopards, have the lowest genome‐wide heterozygosity of all the big cats. This further emphasizes the cheetah's perilous conservation status. Our results provide novel and important information on cheetah phylogeography that can support evidence‐based conservation policy decisions to help protect this species. This is especially relevant in light of ongoing and proposed translocations across subspecies boundaries, and the increasing threats of illegal trafficking.